PERAWATAN HOIST CRANE DENGAN METODE MAINTAINABILITY DAN COSTING UNTUK MENGURANGI BREAKDOWN - Andy Hardianto; Pratikto Pratikto; Lilis Yuliati (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2015)
Abstract PT. ABC is a manufacturing company in the field that requires a crane hoist readiness in every production, with an average of 42.92 hours a breakdown, the necessary methods of treatment that effectively and efficiently, with a critical component bearing, gear, wheel trolley, wire rope, shaft, cable pedant. The time interval is the optimum replacement parts NTN Bearing 304; 51 108 21 days, Talibaja (wire rope) Gustav / Demag O16 x 8 x 36 + 1 stainless core38 day, canvass the motor 45, wheel trolley 89 days, gear 76 a day, the pen as 39 days, the cable pendant 67 danUntuk cost savings component replacement Bearing NTN 304; 51 108 Rp. 689,435.94 and pesentase amounted to 3.34%, Talibaja (wire rope) Gustav / Demag O16 x 8 x 36 + 1 stell core Rp. 3,634,660.00 and a percentage of 2.51%, canvass motorcycle is Rp. 7,948,540.37 and a percentage of 58.88%, wheel trolley Rp. 755,467.50 and a percentage of 11.27, gear Rp. 50,195,101.20 and a percentage of 61.68%, the pen as Rp. 18,110,676.40 and the percentage of 62%, amounting to USD 8,545,480.84 pendant cable and a percentage of 38.47%.